The effect of dilute acid pre-treatment process in bioethanol production from durian (Durio zibethinus) seeds waste - Ghazali K.A.; Salleh S.F.; Riayatsyah T.M.I.; Aditiya H.B.; Mahlia T.M.I. (Institute of Physics Publishing, 2023)
Bioethanol; Biomass; Distillation; Ethanol; Fermentation; Glucose; Hydrolysis; Process control; Waste treatment; Bio-ethanol production; Bioethanol fermentations; Cellulosic biomass; Fermentation process; Lignin structure; Lignocellulosic biomass; Pretreatment process; Substrate concentrations; Enzymatic hydrolysis; acid; biofuel; concentration (composition); enzyme activity; ethanol; fermentation; fruit; glucose; hydrolysis; lignin; phytomass; seed; substrate; waste treatment; yeast; Durio zibethinus